The litentiate degree course in Brazilian Popular Music - CECULT UFRB: Challenges of implementation in the EAD modality - de Vasconcelos, Jorge Luiz Ribeiro (Revista Hipótese, 2022)
In 2021, the Licentiate Degree in Brazilian Popular Music – EaD modality was started at UFRB, an initiative of the CECULT and SEAD university centers, with the support of CAPES. Starting from an innovative proposal of courses in art, culture and their languages, more specifically, from a successful experience of implementing a course for music educators in the classroom mode, the opportunity allowed us to expand a current process of expansion of education to inland cities. We present an account of this experience, and the discussion of some peculiarities and challenges found in this very recent process, problematizing the issues of teaching music and the arts at a distance and online.
Keywords: Musical education; Popular music; Recôncavo da Bahia